Physics matters. gce 'o' level [textbook] 4th edition - Chew, Charles; Chow, Siew Foong Ho, Boon Tiong (Marshall Cavendish Education Singapore, 2013)
Covering the GCE 'O' Level Physics syllabus set by the Ministry of Education, Singapore, this textbook facilitates the effective learning of Physics and makes the subject inspiring and riveting for students through the following features. Lively and engaging Colorful and stunning visuals, real life examples and simple language are used to make the subject come alive to enhance students' learning. Thought provoking facts and activities, and inquiry questions are found throughout the textbook to stimulate students' interest and enable conceptual understanding. Simplifies learning Ample hands-on activities and unique sidebar features are used to simplify concept development, as well as enrich students' understanding of the topic. Fundamental ideas are reinforced through regular summaries and end-of-section tests. Builds exam confidence Challenging worked examples are included to showcase application of concepts. Ample questions are provided at frequent junctures for students' practice, preparing them for assessment. This textbook is supplemented by two volumes of Workbooks and a Practical Book. The Workbooks are designed for self-study and assessment, while the Practical Book contains activities and experiments that prepare students for the new Science Practical Assessment (SPA). The publishers do not recommend the Practical Book for home use due to safety issues and the expense and difficulty in obtaining some of the materials. Answers to most of the textbook problems (those with short answers) are in the back.